GENETIC DIVERSITY ANALYSIS OF Pseudomonas cichorii ISOLATES FROM BRAZIL - DestÃ©fano, Suzete A. L.; Almeida, Irene M. G.; Rodrigues Neto, JÃºlio (REVISTA DE AGRICULTURA, 2015)
GENETIC DIVERSITY ANALYSIS OF Pseudomonas cichorii ISOLATES FROM BRAZIL